TRANSLATION STRATEGY AND ACCURACY OF IDIOMATIC EXPRESSION IN WEDNESDAY SERIES (2022) - Suriadi, M. Agus; Kirana, Puspita Maya (Universitas Gunadarma, 2024)
This study examines the translation strategies and accuracy of idiomatic expressions in the Indonesian subtitles of the Wednesday series. Specifically, it analysed the methods and effectiveness of translating culturally nuanced idioms, highlighting their role in maintaining linguistic and cultural integrity. Using a qualitative method, data were collected by systematically watching the series, transcribing the target language audio, and identifying idiomatic expressions in the source language. Idioms were categorized based on Fernando and Makkai's typology, evaluated using Peter Newmark’s translation methods, and analyzed with Jan Pedersen's strategies. Accuracy was assessed using Nababan's framework. The study identified four types of idioms: pure idioms, semi-idioms, literal idioms, and phrasal verb idioms. Among the 64 idioms analyzed, 25 were pure idioms, 13 semi-idioms, 9 literal idioms, and 17 phrasal verb idioms. Translators employed five of the seven strategies outlined by Pedersen: generalization, direct translation, omission, substitution, and specification, with generalization being most frequent. The subtitle translations achieved high accuracy, with 45 accurate translations, 13 almost accurate, and 6 inaccurate. These findings underline the translators’ proficiency in maintaining the semantic and cultural integrity of idiomatic expressions. However, future research should address limitations such as the scope of data and potential subjective interpretations. This study contributes to translation studies by offering insights into idiom translation in audio-visual media, emphasizing strategies for achieving accuracy and cultural relevance.